ANALISIS KEPUASAN PENGUNJUNG WISATA DENGAN MODEL KANO BERDASARKAN DIMENSI SERVQUAL - Ramadhani, Yuliastuti; Suciandani, Praptiwi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
The aim of the study was to integrate measurement of visitor satisfaction to the service given by management of Pikatan Water Park by using Kano model for identifying proper priority forward performance improvements of each questionnaire. The total which was used to measure was questionnaire consisted of functional question and dysfunctional question that was grouped into servqual dimension (tangible, reliability, responsiveness, assurance, and empathy). The result of 58 respondents who did questionnaire, it was categorized Kano (one-dimensional, must-be, attractive, indifferent, reserve, and questionable). The result of the study according to the respondents, it is obtained that the highest point of tangible dimension, categorized â€œone dimensionalâ€ was 193, whereas other four categories included â€œmust-beâ€ are 63, 73, 127, and 83 res-pectively. According to management, however, tangible dimension categorized â€œone-dimensionalâ€, to increase visitors, it is necessary to give good interest to each questionnaire and to add each reliability dimension in order to increase city budget.